STRATEGI DAN KINERJA INVESTASI DALAM AKTIVITAS PERDAGANGAN INVESTOR ASING VS INVESTOR DOMESTIK - Johannes Maysan Damanik; Eduardus Tandelilin (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This study is aimed to find out the investment strategy and investment performance betwen foreign investrors and domestics investror who have transaction in Indonesia Stock Excange. A Proxy used to see the Investment Strategy and Investment Performance in this study is the Trading Profit from transaction wich has been done by the investors. Investment strategy chossen bt investors can be seen from the investor’s tendency in doing some sales which contains some shareds with positive and negative valued trading profit. Investment Performance is seen from the investor’s capability in producing positive valued trading profit. This study used intra-day transaction data which are transacted by foreign investors and domestic investors. The result of this study found that foreign investors used a momentum when transacting in the stock excange and domestics investor using a contrarian when transacting in the stock excange. This study olso found that there isn’t defferent performance between foreign investors and domestik investors in stock excange transactions activities.